Monsters we met, monsters we made: On the parallel emergence of phenotypic similarity under domestication - Karel Kleisner; Marco Stella (Sign Systems Studies, 2009)
Creatures living under the rule of domestication form a communicative union based on shared morphological, behavioural, cognitive, and immunological resemblances. Domestic animals live under particular conditions that substantially differ from the original (natural) settings of their wild relatives. Here we focus on the fact that many parallel characters have appeared in various domestic forms that had been selected for different purposes. These characters are often unique for domestic animals and do not exist in wild forms. We argue that parallel similarities appear in different groups in response to their interaction with the umwelt of a particular host. In zoosemiotic sense, the process of domestication represents a kind of interaction in which both sides are affected and eventually transformed in such a way that one is more integrated with the other than in the time of initial encounter.